Consumers' trust and values towards halal cosmetics and personal care products - Abu Bakar, Elistina; Rosslee, Nashaqilla Norlee; Muhammad Arif, Afida Mastura; Othman, Mohhidin; Hashim, Puziah (Malaysian Consumer and Family Economics Association, 2017)
Halal is not just applicable to food and drinks consumed internally but also products applied externally. Halal is often associated with products that are safe, clean, healthy and in accordance with the principles of halalan toyyiban. Muslim consumers often face problems to ensure that the products they buy, including cosmetics, are genuinely halal as they can only rely on the certification of the authorities. However, the question is to what extent do Muslim consumers in Malaysia trust the responsible authorities such as Jabatan Kemajuan Islam Malaysia (JAKIM) and the Ministry of Health (MOH) in determining the halal status of a product. In addition, the consumers‟ values are also important to determine consumers’ behaviour. Therefore, the objectives of this paper are to identify consumers’ level of trust towards JAKIM, the Ministry of Health, the international certification bodies and also the producers of cosmetic and personal care products. In addition, this paper will also determine the value the consumers consider when they buy halal cosmetic products. The multiple regression analysis is used to examine whether trust and values are determinant factors of consumers’ behaviour towards halal products. A total of 400 Muslim consumers in Klang Valley participated in this study and they were selected through stratified random sampling. The results showed that trust towards JAKIM is the highest, followed by trust towards International Halal certification agency, the MOH and lastly, the producers. Meanwhile, the values associated with halal cosmetics are the quality, followed by emotional, economic, social and lastly conditional values. However, only two variables which are the trust towards MOH, and also emotional value, are significantly affecting the consumers’ behaviour where the emotional value is the strongest predictive factor. This study is expected to help stakeholders such as JAKIM, the MOH as well as producers of cosmetics products to enhance the Halal industry and therefore increase economy while protecting the welfare of Muslim consumers in Malaysia.